Implementasi Steganografi Metode Least Significant Bit (LSB) untuk Menyembunyikan File Pesan dalam Gambar - Muhammad Naim Al Jumah; Sarimuddin Sarimuddin (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Ease of image manipulation is not something difficult. Images become a more effective communication medium for society. The development of software for image manipulation, increasing crime such as phishing and bullying in cyberspace. The Least Significant Bit method is a steganography method that can be used to encrypt or hide messages in images. Hiding information in various media files such as images is done to maintain the confidentiality of the messages sent. This research implements the Least Significant Bit (LSB) method to hide a message file in an image. This research carries out encryption and description of the message to be sent by inserting a file into the image. This research will also carry out a testing process for the stego image. From the results of tests that have been carried out by carrying out three processes of sending stego image files via copying files with a flash disk, email and sending via WhatsApp with a document model, the results obtained are that stego image files can still be extracted data to get messages that have been encrypted in the image, However, when the stego image file is sent via WhatsApp using the image sending method, the stego image cannot be extracted. This happens because there has been a change in the extension of the file downloaded from WhatsApp. This is also influenced by data changes in the form of file compression from the WhatsApp application. Where every file sent via the WhatsApp application will experience file compression so that data changes will occur